Analysis Of Pioneering Raskin Innovation For The Pattern Of Labor-Intensive Food in North Central Timor District - Ane Rupaiedah; Kismartini Kismartini; Ida Hayu Dwimawanti (International Journal of Social Science and Religion (IJSSR), 2021)
This research is intended to analyze the Pioneering of the Raskin Innovation for Food Labor Intensive Patterns in North Central Timor District. The problem in this research is how the stages of pioneering Raskin innovation for food labor in the North Central Timor district. To answer this problem, various theories are relevant to the research phenomenon. This research uses descriptive qualitative method with data analysis techniques Milles and Huberman. The results of the Raskin Innovation Research on Food Labor Intensive Patterns in North Central Timor Regency, namely: 1.In the Raskin Innovation Initiation phase, PKP was formulated by identifying agricultural problems in TTU Regency so that the Innovation concept was indeed appropriate to answer the problem, then the PKP Raskin innovation adjusted to several criteria, namely new concepts, finance, technical capabilities, and public support. However, in adjustment there are problems that need to be reviewed and improved in the PKP Raskin innovation guidelines.